Analisis Pertumbuhan Ekonomi di Karesidenan Semarang Era Desentralisasi Fiskal - Pujiati, Amin (Economic Journal of Emerging Markets, 2009)
Every regions goverment must be able increasing their own regional income. The finance of resources in fiscal decentralization era, such as: regional original income, general allocation funds and natural resources revenue sharing and tax revenue sharing This research aims to analyze the fiscal decentralization impact to economic growth at regional district in sub provinsi Semarang. The tools of analisis is regression using panel data with Generalized Least Square (GLS) method and Fixed Effect model. It uses district-level data and supplied by the Indonesian Central Bureau of Statistics during 2002 - 2006 The regression result shows that regional income, natural resources revenue sharing and tax revenue sharing, and labour forces have positive impact on economic growth at regional district in sub provinsi Semarang.General allocation funds has negative effect towards economic growth at regional district in sub provinsi Semarang. Fiscal decentralization brings more advantages for regions to manage their own fiscal capacities. The regions governments must be have informational advantages concerning resource allocation with optimal Keywords: Fiscal Decentralization, economic growth, Fixed Effect Model